CUL4B Promotes Breast Carcinogenesis by Coordinating with Transcriptional Repressor Complexes in Response to Hypoxia Signaling Pathway. Issue 10 (16th March 2021) - Huang, Wei; Zhang, Jingyao; Huo, Miaomiao; Gao, Jie; Yang, Tianshu; Yin, Xin; Wang, Pei; Leng, Shuai; Feng, Dandan; Chen, Yang; Yang, Yang; Wang, Yan
Abstract: Cullin4B (CUL4B) is a scaffold protein of the CUL4B‐Ring E3 ligase (CRL4B) complex. However, the role of CUL4B in the development of breast cancer remains poorly understood. Here it is shown that CRL4B interacts with multiple histone deacetylase (HDAC)‐containing corepressor complexes, including MTA1/NuRD, SIN3A, CoREST, and NcoR/SMRT complexes. It is demonstrated that CRL4B/NuRD(MTA1) complexes cooccupy the E‐cadherin and AXIN2 promoters, and could be recruited by transcription factors including Snail and ZEB2 to promote cell invasion and tumorigenesis both in vitro and in vivo. Remarkably, CUL4B responded to transformation and migration/invasion stimuli and is essential for multiple epithelial‐mesenchymal transition (EMT) signaling pathways such as hypoxia. Furthermore, the transcription of CUL4B is directedly activated by hypoxia‐inducible factor 1 α (HIF1 α ) and repressed by the ER α ‐GATA3 axis. Overexpressing of CUL4B successfully induced CSC‐like properties. Strikingly, CUL4B expression is markedly upregulated during breast cancer progression and correlated with poor prognosis. The results suggest that CUL4B lies at a critical crossroads between EMT and stem cell properties, supporting CUL4B as a potential novel target for the development of anti‐breast cancer therapy. Abstract : Cullin4B (CUL4B) is identified as a master regulator in promoting breast cancer carcinogenesis, metastasis, and stemness. The CUL4B‐Ring E3 ligase/NuRD (MTA1) complexes repress ER α, E‐cadherin, and AXIN2 through epigenetic regulatory mechanisms. The transcription of CUL4B is stimulated by HIF‐1 α and suppressed by the ER α ‐GATA3 axis. These findings support the pursuit of CUL4B as a promising therapeutic target for breast cancer.